2007
DOI: 10.1002/ajp.20500
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of salivary pH in sympatric wild lemurs (Lemur catta and Propithecus verreauxi) at Beza Mahafaly Special Reserve, Madagascar

Abstract: Chemical deterioration of teeth is common among modern humans, and has been suggested for some extinct primates. Dental erosion caused by acidic foods may also obscure microwear signals of mechanical food properties. Ring-tailed lemurs at the Beza Mahafaly Special Reserve (BMSR), Madagascar, display frequent severe tooth wear and subsequent tooth loss. In contrast, sympatric Verreaux's sifaka display far less tooth wear and infrequent tooth loss, despite both species regularly consuming acidic tamarind fruit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Among the maxillary teeth, left and right P3 through M1 show significantly greater wear at BMSR. These three tooth positions are frequently lost owing to excessive wear at BMSR, a pattern associated with processing mechanically and physically challenging foods, specifically fruit of the tamarind tree (T. indica), an important fallback food among ring-tailed lemurs inhabiting several riverine gallery forests of southern Madagascar [e.g., Cuozzo & Sauther, 2004, 2006aCuozzo et al, 2008;Gemmill & Gould, 2008;Mertl-Millhollen et al, 2006;. Among the mandibular teeth, all tooth comb positions at BMSR show significantly more wear than in the captive sample.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the maxillary teeth, left and right P3 through M1 show significantly greater wear at BMSR. These three tooth positions are frequently lost owing to excessive wear at BMSR, a pattern associated with processing mechanically and physically challenging foods, specifically fruit of the tamarind tree (T. indica), an important fallback food among ring-tailed lemurs inhabiting several riverine gallery forests of southern Madagascar [e.g., Cuozzo & Sauther, 2004, 2006aCuozzo et al, 2008;Gemmill & Gould, 2008;Mertl-Millhollen et al, 2006;. Among the mandibular teeth, all tooth comb positions at BMSR show significantly more wear than in the captive sample.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term study of this population has documented a series of dental health patterns [Cuozzo & Sauther, 2004, 2006aCuozzo et al, 2008;Sauther et al, 2002Sauther et al, , 2006, including a high frequency of severe tooth wear and antemortem tooth loss. Beginning in 2003, F. P. C. and M. L. S. initiated a systematic study of the dentition of this lemur population, in part to identify the proximate causes of this phenomenon [e.g., Cuozzo & Sauther, 2004, 2006aCuozzo et al, 2008;. At BMSR, more than 20% of all individuals studied have lost at least one tooth.…”
Section: Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely in a study at Beza Mahafaly Special Reserve, Yamashita [2008] found only negligible amounts of tannins (1/135 assays) in gallery and deciduous forest plant foods consumed by ring-tailed lemurs at this site over a 13-month period. However, the fruit and leaves of Tamarindus indica, an extremely important food resource and fallback food for L. catta in gallery forests [Sauther, 1993[Sauther, , 1998Yamashita, 2002;Simmen et al, 2006b;Sauther and Cuozzo, in press] contain relatively high tannin concentrations [Watt and Breyer-Brandwijk, 1962;Simmen et al, 2003], and Cuozzo et al [2008] suggest that dietary tannins from tamarind fruit might be a contributing factor to a high frequency of severe tooth wear and tooth loss found in a large sample of L. catta examined at Beza Mahafaly Special Reserve.…”
Section: Introductionmentioning
confidence: 99%